Issues of construction health and safety in developing countries: a case of Jordan (Construction Economics and Building, 2013)
The construction industry is widely regarded as one of the most significant interms of its impact on health and safety (H&S). Recent findings suggestthat in developing countries H&S awareness and performance is low. In this paper,the current state of H&S on construction sites in Jordan was explored usinga two-part investigation. The first part introduces the area of research in aliterature based study of on-site safety. The second part is a case study onthe Jordanian construction industry and its current H&S practices. Primary datawas collected from field visits, expert interviews and semi-structuredquestionnaires. Supporting secondary data was collected from archival studiesand related research literature. The research findings highlight a lack of governmentcommitment exemplified by regulations, policies and legal constraints thatlimit the operational efficiency of those government departments responsiblefor H&S management, and hindering the development of good H&S practice.Research results also highlight the key constraints of good H&S practice fromthe perspective of construction contractors.The study concludes with discussion ofpotential solutions toimprove H&S performance on construction sites in Jordan.